2014
DOI: 10.1111/gtc.12209
|View full text |Cite
|
Sign up to set email alerts
|

BNIP‐2 binds phosphatidylserine, localizes to vesicles, and is transported by kinesin‐1

Abstract: BNIP-2 shows high homology with the Cayman ataxia protein, caytaxin, which functions as a kinesin-1 adapter bridging cargos and kinesin light chains (KLCs). BNIP-2 is known to induce cell shape changes when over-expressed in culture cells, but its physiological functions are mostly unknown. BNIP-2 interacts with KLC through the conserved WED motif in the N-terminal region of BNIP-2. Interaction with KLC and transportation by kinesin-1 are essential for over-expressed BNIP-2 to elongate cells and induce cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In this study, we show that KLC1 interacts with WAVE1, (BNIP-2), and protein interacting with APP tail 1 (PAT1) [1,8,10,14,21,22]. In this study, we have identified that WAVE1 interacted with the TPR domain of KLC1.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, we show that KLC1 interacts with WAVE1, (BNIP-2), and protein interacting with APP tail 1 (PAT1) [1,8,10,14,21,22]. In this study, we have identified that WAVE1 interacted with the TPR domain of KLC1.…”
Section: Discussionmentioning
confidence: 70%
“…Potential Lipid-Binding Region in Y BCH. Previously it was shown that BNIP-2 binds to phosphatidylserine (a phospholipid) via its BCH domain, which implies that the BCH domain has lipid-binding properties (33). Moreover, the Sec14 domain of neurofibromin was highlighted in our N-terminal domain structural search as being homologous with the BCH domain.…”
Section: Resultsmentioning
confidence: 79%
“…In addition, caytaxin is abundantly expressed in neurons of the cortex, cerebellum, hippocampus, olfactory bulb, and basal ganglia. 33 Akamatsu and colleagues used full-length caytaxin as a bait to perform yeast two-hybridization with mouse adult brain cDNA, 40 and found that caytaxin can drive the protein light chain of kinesin-1 through its N-terminal ELEWED sequence (amino acids 115-120) and participate in axonal transportation. Kinesin, a key molecule for axonal transportation, can be combined with a variety of linker molecules, such as TRAK1/2 and JIP1, to regulate mitochondrial axonal transportation of amyloid precursor protein.…”
Section: Ischemic Stroke Activates the Death-associated Protein Kinasmentioning
confidence: 99%